Evaluación de bioestimulantes a diferentes dosificaciones en el cultivo de Rosa (Rosa sp.) de la variedad Mondial® en la zona de Pupana norte, Saquisili, Cotopaxi 2023 – 2024 - Chancusig Viturco, Kevin Alexander (2024)
The Mondial rose is a variety of flower appreciated in the market, by this reason this research was carried out in order to improve its production and quality. Due to this, a new alternative was sought for rose producers and thus increase the productivity and quality of the product. The current investigation was carried out in the northern Pupana neighborhood, Saquisilí Canton, Cotopaxi Province, with the objective of evaluating biostimulants at different dosages in the cultivation of rose (Rosa sp.) of the Mondial kind. The research is experimental by manipulating two variables, qualitative when describing complex natural events and quantitative when collecting numerical data on the variables. Its statistical analysis was carried out with the InfoStat program where two biostimulants were used: Evergreen and Foliplus applied foliarly every 30 days during the variety cycle, arranged in a completely randomizer design with a 2x3+1 factorial arrangement with three observations, where factor A has two levels (a1 and a2) and factor B has three levels (b1, b2 and b3) and plus the additional one (control), resulting in 21 experimental units. The variables evaluated were length of the floral stem, caliber of the floral stem, length of the flower bud, diameter of the flower bud, days to harvest, vase life, yield, pH, electrical conductivity, Ca, NO3, K and Na. For data assessment, a statistical analysis was performed where the sources of variation that indicated statistical significance were performed with a 5% Tukey test.